NURSE CONTRIBUTIONS TO THE SOCIAL INCLUSION OF PEOPLE WITH MOTOR DISABILITIES IN HOME VISITS (REMUNOM, 2025)
This project emphasizes the challenges nurses face when monitoring people with motor disabilities through home visits in primary care. Social inclusion is essential for the quality of life of these individuals, and nurses play a key role in providing humanized care, rehabilitation, and promoting autonomy, thus contributing to a fairer society. The study will be conducted through an integrative literature review, using databases such as VHL and Google Scholar, with articles from 2019 to 2023. The analysis will seek to understand how nursing contributes to social inclusion, identify challenges, and propose perspectives for improvement.